Pelatihan Pengelolaan Daun Kering Menjadi Pupuk Kompos di SMA Muhammadiyah 1 Pekanbaru - Rury Bunga Dahliati; Audhytia Romadona; Qonaah Nuryan Arif (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The management of dry leaves into compost at SMA Muhammadiyah 1 Pekanbaru as part of the implementation of the P5 program is an innovative step in reducing organic waste and maintaining the cleanliness of the school environment. The composting process, which involves students, not only produces beneficial natural fertilizer but also provides learning experiences on waste management and organic farming. Additionally, the use of EM4, sugar, and water helps accelerate the decomposition of organic materials, allowing the compost to be ready for use in a shorter time. This program benefits the school, students, and the community in terms of cleanliness, sustainability, and environmental education. This initiative aims to raise environmental awareness and encourage its application in daily life.